Articulações territoriais: uma cartografia da atenção à população em situação de rua - Magalhães, Julia Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The attention to the social vulnerable and homeless people demands devices for qualifying the intervention of technical teams in Public Policy. This is an important challenge for the field of mental health, considering the principles of universality, equity and comprehensive care of the Brazilian health system - SUS. Intersectoral coordination is crucial in this field because social assistance is an area which has extensive experience working with this population. Besides, given the fragility of the links between hostels and health facilities, it is difficult to ensure continuity of health care of this population, with high mobility, low institutionalization and housing and documentation multiple conditions. In order to increase the knowledge of existing practices in this field, we made a cartography of the actions of the Consultório na Rua Program agents. Cartography helps us analyze local discourses, explore the boundaries and map lines of flight, which lead us to glimpse other modes of care and life creeping with other forms of composition with power. Field research was conducted at the primary care service in the center of São Paulo. The research made possible to question this health promotion practices, with their specificities and peculiarities, and identify the strengths of both subjugation and standardization as the emancipatory inventive and autonomous participation. There is a description of work agents processes, which can create a clinical work: visits to the field, and analysis of the concept of territory and the way it crosses the health care of this population; reception; meetings. Ana analysis of the objectives and working conditions; and connections and tensions with other departments. We conclude that this program and the agents perform a clinical work because their practice involves an important listening function and bonds with...

Na atenção à população em situação de rua e vulnerabilidade social, percebe-se a necessidade permanente de construção de dispositivos para a qualificação da intervenção das equipes técnicas nas Políticas Públicas. Isso se coloca como um desafio importante para a área da Saúde Mental, considerando os princípios de universalização, equidade e integralidade do cuidado do Sistema Único de Saúde (SUS). A articulação intersetorial é fundamental nesse campo, pois a Assistência Social é uma área que possui ampla experiência de trabalho com essa população; e, diante da fragilidade dos vínculos entre os albergues e as unidades de saúde, é difícil garantir a continuidade da atenção à saúde dessa população, com grande mobilidade, pouca institucionalização e condições múltiplas de moradia e documentação. A fim de aprofundar o conhecimento sobre as práticas existentes nesse campo, cartografamos modos como são realizados atendimentos por agentes comunitários do Consultório na Rua. A cartografia nos ajuda a analisar as discursividades locais, explorar os limites e mapear linhas de fuga, que nos levam a vislumbrar outros modos de cuidado e de vida se insinuando, com outras formas de composição com o poder. O campo da pesquisa foi realizado na Unidade Básica de Saúde da República, situada no centro da cidade de São Paulo. Problematizamos essa composição tomada pelas práticas de promoção da saúde, com suas especificidades e peculiaridades, e identificamos as forças tanto de submetimento e padronização quanto as emancipatórias de participação inventiva e autônoma. Apresentamos uma descrição dos processos de trabalho, que mais apareceram no contato com as agentes, e que são potentes na consolidação de um trabalho clinico: as idas à campo, e aprofundamos na análise do conceito de território e a maneira como ele atravessa a atenção à saúde dessa...
Keywords: Sistema Único de Saúde (Brasil); Politicas publicas; Saude mental; Pessoas desabrigadas; Public policy